La vida como concepto político: una lectura de Foucault y Deleuze - Garcés, Marina (Athenea Digital, 2005)
The relationship between life and politics became increasingly central to theory and praxis as the 20th century progressed. Today, it is at the core of all philosophical, political and economic analyses that bear on the question of biopower or biopolitics. In this article, we propose a reading of some of the main texts of Foucault and Gilles Deleuze in which their reflections on life has a political dimension: resistance, in the case of Michel Foucault, and liberation, in the case of Gilles Deleuze. Their respective ontological constructions are different, but they share an orientation to thinking “in another way” and writing for a “missing public”. In both these writers' cases, the concept of life as a political concept is the clue to understanding their position.